Bad Jobs, Bad Health? How Work and Working Conditions Contribute to Health Disparities. (August 2013) - Burgard, Sarah A.; Lin, Katherine Y.
In this review, we touch on a broad array of ways that work is linked to health and health disparities for individuals and societies. First focusing on the health of individuals, we discuss the health differences between those who do and do not work for pay, and review key positive and negative exposures that can generate health disparities among the employed. These include both psychosocial factors like the benefits of a high-status job or the burden of perceived job insecurity, as well as physical exposures to dangerous working conditions like asbestos or rotating shift work. We also provide a discussion of the ways differential exposure to these aspects of work contributes to social disparities in health within and across generations. Analytic complexities in assessing the link between work and health for individuals, such as health selection, are also discussed. We then touch on several contextual-level associations between work and the health of populations, discussing the importance of the occupational structure in a given society, the policy environment that prevails there, and the oscillations of the macroeconomy for generating societal disparities in health. We close with a discussion of four areas and associated recommendations that draw on this corpus of knowledge but would push the research on work, health, and inequality toward even greater scholarly and policy relevance.